Notarial Authority and Legal Accountability in Sharia Banking Contracts: A Doctrinal Study - Agung Iriantoro (Jurnal Hukum, 2025)
The purpose of this study is to examine and analyze the role and responsibilities of notaries in drafting Islamic banking agreements. This study uses a doctrinal legal approach. The findings show that notaries have the authority to prepare authentic deeds for Islamic banking contracts. These deeds serve as strong legal evidence in resolving disputes in the context of Islamic banking. The responsibility of notaries in preparing Islamic banking agreements includes three legal aspects. First, under civil law, Article 84 of the Notary Law outlines the civil liability of notaries. Second, under administrative law, Article 85 of the Notary Law provides that if a notary makes an error when drafting a deed, they may be subject to administrative sanctions in accordance with the Notary Law and its implementing regulations. Third, in terms of criminal law, if a notary commits an act that constitutes a criminal offense as defined in the Criminal Code, they may face criminal sanctions accordingly. The study suggests that sharia training and certification for notaries should be made standard, especially for those involved in Islamic finance.